Análise comparativa de vegetação lenhosa do ecossistema campina na Amazônia brasileira - Ferreira, Carlos Alberto Cid (Instituto Nacional de Pesquisas da Amazônia - INPA, 2009)
Amazonian campinas are sclerophytic vegetation occurring in white sand soils. Although in the beginning they were just mentioned for the rio Negro basin, it is now know that the campinas are widely distributed in the Amazon and some other areas of Tropical America. Amazonian campinas occur as enclaves in areas with dominated by other vegetation types such as rain forests, savannas or campinarana forests. The sandy soils colonized by campinarana plants could be of different origins, such as: a) beds of ancient bodies of water that dry ; b) the sandy profiles derived from the erosion of sandstones from the Guiana Shield or the Brazilian Shield, and; c) ancient sand dunes of eolian origin. This present thesis is aiming to describe and compare from the floristic and phytosociologic point of view, nine Amazonian campinas. Only arboreal and shrubby species with diameter at breast height (DAP) > 5 cm were studied. The nine campinas studied contained, 252 species belonging to 121 genera and 44 families. The families of greatest floristic abundance were Fabaceae, Mytaceae, Rubiaceae, Clusiaceae, Malpighiaceae, and Annonaceae. The genera of most importance were Clusia, Emmotum, Pagamea, Tapirira, Eugenia, Matayba, Myrcia and Ouratea. The nine sampled areas exibited a high proportion of unique species: 72.6% of the species were just registered in one of the campinas. The high proportion of exclusive species resulted in a great floristic comparative distance among the campinas (Jaccard distance ranging from 0.471 to 0.942). In contrast, seven species (2.8% of total) occurred in more than five campinas. These species have wide neotropical distribution and occur in different physiognomies: Humiria balsamifera Aubl., Emmotum nitens Miers, Pagamea guianensis Aubl., Tapirira guianensis Aubl., Byrsonima crassifolia (L.) Kunth., Ouratea spruceana Engl. e Alchornea discolor Poepp. The analysis of the species distribution together with the floristic similarity and MDS analysis have found some phytogeographic patterns for the Amazonian campinas, such as: a) great floristic afinity among Amazonian campinas and the Guiana Shield vegetation and Venezuela-Colombia Llanos; b) campinas in contact with Amazon basin and Brazilian Shield, like the Serra do Cachimbo ones, show greater influence from the Cerrado vegetation; c) campinas from eastern Amazon has shown greater influence from the Guiana and Brazilian Shield floras; d) Low afinity between the Amazonian campinas and restinga vegetation from the Atlantic cost; e) Amazonian campinas from the Brazilian western extreme, like Cruzeiro do Sul (Acre), are significantly different from the other ones. The results of this work reinforce the need of biodiversity conservation programs for the Amazonian campinas due to the great floristic divergence observed among them, large endemic potential and its occurrence on restricted isolated spots.
Keywords: Composição florística; Fitossociologia; Campina; Amazônia